Unwanted sea migrants across the EU border: The Canary Islands. (November 2017) - Vives, Luna
Abstract: In the early 2000s, the Canary Islands emerged as the main gateway for unwanted sea migrants from Senegal into Spain. In this paper, I draw from a year of multi-sited ethnographic work to discuss the relationship between state actions to secure the border against these migrants, on the one hand; and smugglers and migrants' efforts to subvert those actions, on the other. My argument is that the relationship between the two is mutually constitutive: anti-immigration policy is a reaction to the actions of unwanted migrants, and unwanted migrants adapt to state efforts to seal the border against unwanted migration by finding and exploiting spaces of opportunity in the border. In the context of sea migration from Senegal to the Canary Islands, 2005 marks a major shift in this relationship. That year the European Union adopted a new framework for migration control (the Global Approach to Migration and Mobility), Frontex became operational, and Spain and Senegal deepened their cooperation to stop unwanted Europe-bound sea migration. This forced unwanted migrants to find creative ways to enter EU territory. I argue that combining the institutional and migrant perspectives allows us to explore the decentering of the state in the contemporary anti-immigration border regime, the emerging spatialities of the contemporary border, and understand the migrant's journey. This perspective also illuminates the messiness, violence, and multiplicity of interests involved in the bordering of Europe. Highlights: 2005 marked a shift in anti-immigration border policy along the Southern EU's maritime border. Institutional anti-immigration efforts and migrants' strategies to cross the border are mutually constitutive. Combining state and migrant perspectives highlights the implications of anti-immigration efforts.